rom the axioms of a vector space, prove that −(v + w) = (−v) + (−w), for all vectors v, w
Question
From the axioms of a vector space, prove that - (v + w) = (-v) + (-w), for all vectors v, w.
Solution
Sure, here is the proof:
-
We know that for any vector v, v + (-v) = 0. This is the definition of additive inverse in a vector space.
-
Now, consider the vector v + w. Its additive inverse is -(v + w), which means (v + w) + (-(v + w)) = 0.
-
We also know that vector addition is associative, so we can write this as v + (w + (-(v + w))) = 0.
-
Now, we can use the definition of additive inverse again to replace w + (-(v + w)) with -v. This gives us v + (-v) = 0, which we know is true.
-
Therefore, -(v + w) = -v + -w.
This proof relies on the axioms of a vector space, specifically the existence of an additive inverse for every vector and the associativity of vector addition.
Similar Questions
Let v be a vector and let k be a scalar. From the axioms of a vector space, prove that if kv = 0 theneither k = 0 or v = 0.
Let x and y be two vectors from Rn. Show that x − y andx + y are orthogonal if and only if ∥x∥ = ∥y∥
Let uˉ=⟨0,−2⟩,vˉ=⟨4,3⟩, and wˉ=⟨0,-4⟩. Find the vector xˉ that satisfies 5uˉ−vˉ+xˉ=2xˉ+wˉ In this case, xˉ=
Prove that if W is a subspace of a finite dimensional vector space V, then dim(W) ≤ dim(V).
Suppose {v,w} is a linearly independent set in the vector space V.Then the set {v,v+w} is also linearly independent.A. TrueB. False
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.